2021
DOI: 10.1088/1742-6596/2049/1/012075
|View full text |Cite
|
Sign up to set email alerts
|

Flexural Capacity of Concrete Beam Reinforced with GFRP Bars

Abstract: This paper proposes an analytical study to predict the flexural capacity of structure elements reinforced with glass fibre reinforced polymer (GFRP) bars. A nonlinear stress-strain curve of concrete is employed to consider the contribution of concrete under compression. The analytical calculation is validated against a published experiment, and the results are also compared to the ACI 440.1R-15 code. The results showed that the rupture modes predicted in the analytical study were comparable to those of the exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…The results showed that the predicted rupture modes by the analytical analysis matched the rupture modes seen in the experiment as recorded in Table 1. Furthermore, flexural capacity obtained using Todeschini's nonlinear curve [5] for specimens with reinforcement ratios greater than the balanced reinforcement ratio performed better than that obtained using ACI code [8] as shown in Figures 6 and 7.…”
Section: Recent Studies 21 Glass Fiber-reinforced Polymer (Gfrp)mentioning
confidence: 86%
See 3 more Smart Citations
“…The results showed that the predicted rupture modes by the analytical analysis matched the rupture modes seen in the experiment as recorded in Table 1. Furthermore, flexural capacity obtained using Todeschini's nonlinear curve [5] for specimens with reinforcement ratios greater than the balanced reinforcement ratio performed better than that obtained using ACI code [8] as shown in Figures 6 and 7.…”
Section: Recent Studies 21 Glass Fiber-reinforced Polymer (Gfrp)mentioning
confidence: 86%
“…El Refai et al (2015) [3] studied the structural performance of hybrid reinforced concrete beams. Three beams with only GFRP reinforcement and six other beams reinforced with a combination of GFRP and steel bars were tested to investigate the flexural performance as shown in Figure 1 Ridwan et al ( 2021) [5] proposed an analytical approach to predict the flexural capacity of a beam reinforced with GFRP bars. This approach was based on strain compatibility and internal forces equilibrium.…”
Section: Recent Studies 21 Glass Fiber-reinforced Polymer (Gfrp)mentioning
confidence: 99%
See 2 more Smart Citations